Fostering Professionalism in Prospective Early Childhood Teachers through Practice-Based Edupreneurship - Syifauzakia, Syifauzakia; Sumantri, M. Syarif; Dhieni, Nurbiana; Wulan, Sri (GENIUS: Indonesian Journal of Early Childhood Education, 2025)
The formation of the professionalism of prospective Early Childhood Education (ECE) teachers requires a learning approach that integrates theory and practice contextually. This study aims to evaluate practice-based learning in the Edupreneurship course as a strategy to strengthen the professionalism of prospective ECE teachers. This study uses a descriptive qualitative approach with an evaluative study design. Data were obtained through pre-tests, learning observations, project documents, and individual student reflections during 16 lecture meetings. The results of the study show five main transformations: (1) change in perception and increased motivation to become edupreneur, (2) strengthening practical competencies through the production of educational media, (3) mastery of digital skills, (4) increasing teamwork collaboration, and (5) resilience and problem-solving ability in facing real challenges. These findings show that education-based entrepreneurship projects not only train entrepreneurial skills, but also form the professional character of prospective early childhood education teachers who are adaptive, creative, and resilient. It is recommended that this model be systematically integrated into the early childhood education curriculum and developed in the context of cross-disciplinary learning in the future.